A Study of the Arabic and English Composing Processes of Emirati School Students: A Socio- Cognitive Approach - Albakri, Rehab Helmi (2016)
The purpose of the study was to investigate the strategies employed by Emirati school students during the composing processes of Arabic and English written performance. In addition, the study focused on the factors affecting the composing process such as gender, age and first language. The theoretical framework of the study was the socio-cognitive approach introduced by Atkinson (2002) which focuses on the interaction between the social and cognitive dimensions of language learning. To achieve the purpose of the study, a qualitative research approach was used to collect and analyze data. The data was collected from an Arabic private school in Ajman in the United Arab Emirates and the participants consisted of four supervisors (two Arabic and two English supervisors) working at public and private schools and eight students; four from grade 9 (2 boys and 2 girls) and four from grade 11 (2 boys and 2 girls). The research instruments consisted of think-aloud protocol, semi-structured interviews and students’ written products. The think-aloud protocol was used to investigate the internal processes that take place in the mind of the students during composing in Arabic and English. The semi-structured interviews were conducted with the students as retrospective interviews to explore their attitudes towards writing and with the supervisors to investigate their role in enhancing students' writing skills and to throw light on the way textbooks were selected and deployed. To analyze the strategies used by students during their composing of the Arabic and English texts, Mu’s (2005) and Kim’s (2014) taxonomies were adapted to suit the purposes of the study. The Arabic and English written products resulting from students’ verbalization in the think-aloud were analyzed using Jacobs' et al. (1981) scale to rate the English texts and AlHalak's (2009) scale to rate the Arabic texts. An interpretive approach was used to analyze the interviewees' answers to the semi-structured questions, to describe the strategies used by students, and to discuss the ratings of the Arabic and English written products. The findings of the study indicated that students mainly used cognitive and meta-cognitive strategies while composing in Arabic and English, whereas they lack other strategies like revision and editing strategies. Also, the findings showed no indications of the effect of gender and age on the written performance, while they highlighted other factors such as the content of the textbook, teacher's performance, the teaching approach, and students' problems. In addition, the results of data analysis showed to some extent the influence of Arabic proficiency in enhancing English writing. Understanding the factors affecting the composing process will help provide solutions to overcome learners' problems and improve their strategies while writing.